HEPATOPROTECTIVE EFFECT OF MINT AGAINST HEPATOTOXICITY, INDUCED BY CHLOROQUINE, IN MALE ALBINO MICE: RCT - Khalid, Sumbal; Fazal, Ayesha; Kanwal, Shumaela (Journal of Ayub Medical College Abbottabad, 2024)
Background: Many drugs have been associated with hepatotoxicity worldwide. This hepatotoxicity occurs due to oxidative stress generated by those drugs. Hence, different plants, which have antioxidant effects, can be used to prevent hepatotoxicity. The objective was to find out the hepatoprotective effect of mint, against chloroquine induced hepatotoxicity, due to its antioxidant potential. Methods: For that randomized controlled trial study, ninety male albino mice were obtained and were divided randomly into three groups, with each group containing 30 mice. Group A was the control group. So, no intervention was done on mice of Group A. Group B and C were the experimental groups. Group B mice were given chloroquine only. The mice of Group C were given both chloroquine and mint extract. The single oral dose of chloroquine, 970 mg/ kg of body weight, was given to the mice of group B, on the 9th day of the experiment. The ethanolic extract of mint, at the dose of 1 gm/kg, was given consecutively from day 1 to day 8 of the experiment to Group C mice. Then chloroquine (970 mg/kg of the body weight) was given on nineth day to Group C. The ethanolic extract was then continuously given from day 10 to day 16 of the experiment, followed by chloroquine administration, to those mice. The blood samples were collected on 17th day by terminal intracardiac sampling technique. Data analysis was done by SPSS version 20. Results: Group B mice showed highly significant rise in serum ALP and significant decrease in serum albumin, as compared to those of group A. Serum AST and ALT, however, raised insignificantly. Hence, mild hepatotoxicity was induced in group B mice. On the other hand, malondialdehyde, was found to be highly significantly raised in group B mice. While, serum glutathione peroxidase was found to be declined highly significantly in group B mice, which showed oxidative stress induction. The mice of group C showed highly significant decrease in serum ALP and significant decline in serum AST. They showed significant raise in serum albumin. Serum malondialdehyde, however, declined highly significantly and serum glutathione peroxidase raised highly significantly in group C. These results in group C occur due to antioxidant action of mint. Conclusion: Mint revealed hepatoprotective effect due to its antioxidant potential, against chloroquine induced mild hepatotoxicity.